ON COMPLETNESS OF EIGENVECTORS FOR DIRAC TWO PARAMETER BOUNDARY PROBLEM - Sahakian, G. H. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2002)
The Parseval identity is proved for elements of energetic space L^2_Δ_0(I), born by two-parametric Dirac system.